Solid Solutions LnxU1−xC2 with Ln = Tb, Dy, Ho, Tm, and Lu Showing Ideal Vegard Behavior - Christian Tobeck; Heiko Wende; Uwe Ruschewitz (Inorganics, 2023)
The reaction of UO2 with the respective lanthanide metal and purified graphite in an arc-melting furnace led to the formation of solid solutions of the composition LnxU1−xC2, with Ln = Tb, Dy, Ho, Tm, and Lu. They all crystallize in the tetragonal CaC2 type structure (I4/mmm, Z = 2). Elemental analyses of selected samples (EDX) confirm that the composition of the resulting solid solution is in reasonable agreement with the nominal (weighed-in) composition of the starting materials, i.e., a significant evaporation of the lanthanide metals during the arc-melting synthesis does not occur. The lattice parameters of the solid solutions were extracted using Le Bail fits of high-resolution synchrotron powder diffraction data (beamline P02.1, DESY, Hamburg, Germany; beamline BL 09, DELTA, Dortmund, Germany), revealing ideal Vegard behavior for all five solid solutions. XANES investigations on all compounds at the Ln-LIII and U-LIII edges reveal that the occupancies of the U-6d orbitals decrease with increasing x, whereas the occupancies of the Ln-5d orbitals increase, pointing to an electron transfer from the uranium to the lanthanide cations. Examination of the shifts of the absorption edge (E0) leads to the same finding.